2016
DOI: 10.1177/1098612x15623824
|View full text |Cite
|
Sign up to set email alerts
|

Detection of feline coronavirus spike gene mutations as a tool to diagnose feline infectious peritonitis

Abstract: Objectives Feline infectious peritonitis (FIP) is an important cause of death in the cat population worldwide. The ante-mortem diagnosis of FIP in clinical cases is still challenging. In cats without effusion, a definitive diagnosis can only be achieved post mortem or with invasive methods. The aim of this study was to evaluate the use of a combined reverse transcriptase nested polymerase chain reaction (RT-nPCR) and sequencing approach in the diagnosis of FIP, detecting mutations at two different nucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 55 publications
3
44
0
Order By: Relevance
“…Molecular methods have been used for detection of FCoV RNA in the effusions of cats with suspected FIP (Gut et al, 1999;Simons et al, 2004;Hornyák et al, 2012;Soma et al, 2013;Doenges et al, 2017;Felten et al, 2017;Longstaff et al, 2017). However, these methods display similar issues related to the diagnostic performances (lack of sensitivity and specificity).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular methods have been used for detection of FCoV RNA in the effusions of cats with suspected FIP (Gut et al, 1999;Simons et al, 2004;Hornyák et al, 2012;Soma et al, 2013;Doenges et al, 2017;Felten et al, 2017;Longstaff et al, 2017). However, these methods display similar issues related to the diagnostic performances (lack of sensitivity and specificity).…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous mutations of the S gene [6], ORF3abc [7,8], and ORF7ab [9,10] in the FCoV genome allow virions to efficiently replicate in macrophages and monocytes, ultimately resulting in FIPV [11]. Detection of FCoV S gene mutations is considered as a tool to diagnose FIPV [12,13]. FIP is typically characterized by a fibrinous and granulomatous serositis, protein-rich serous effusions, and pyogranulomatous lesions in several organs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Two amino acid substitutions, M1058L and/or S1060A corresponding to nucleotide mutations 23531A>T/C and 23537T>G respectively in the S gene, together distinguished FCoVs found in the tissues of FIP cats from those found in the faeces of healthy cats without FIP in > 95% of cases. A subsequent study, which compared detection of FCoV by RT-qPCR alone to detection of FCoV by RT-qPCR combined with sequence analysis to confirm the presence of nucleotide mutations 23531A>T/C and 23537T>G, concluded that the addition of an assay for S gene mutation analysis did not alter the specificity of the FIP diagnosis, which was already 100%, but did decrease the sensitivity from 9.4 to 6.3% for serum/plasma samples and from 72 to 64% for effusion samples [19]. However, we have shown that the nucleotide mutations 23531A>T/C and 23537T>G are likely to be markers of systemic FCoV infection rather than FIP per se, being present in 91% of the FCoV-positive tissue samples from cats with FIP and 89% of the FCoV-positive tissue samples from cats without FIP [20].…”
Section: Introductionmentioning
confidence: 99%